CO2 Selective Water Gas Shift Membrane Reactor : Modeling and Simulation - Sang Kompiang Wirawan; Derek Creaser; I Made Bendiyasa; Wahyudi Budi Sediawan (Department of Chemical Engineering, Universitas Gadjah Mada, 2012)
The concept of a CO2 selective water gas shift (WGS) membrane reactor has been modeled and simulated by a one-dimensional reactor and transport process in the membrane. The model was used to investigate the effect of temperature, total pressure, membrane thickness and area on the reactor performance. A Silicalite-1 membrane was considered to be integrated with the WGS reactor. The mass transport through the membrane was described by surface diffusion. Air was used as sweep gas on the permeate side of the membrane. The catalytic WGS kinetics were for a commercial Cu/ZnO catalyst for the lower-temperature WGS reaction. The WGS membrane reactor was sized to produce H2 sufficient for the production of 10 kW electrical power from a fuel cell. The modeling and simulation results showed that the WGS membrane reactor with a silicalite-1 membrane was capable of decreasing the CO concentration to about 675 ppm which is 70% less than that achievable at equilibrium conversion, but it would come at the cost of unacceptable H2 loss. Based on a minimum target of H2 loss, the optimum outlet CO concentration achieved by the silicalite-1 membrane reactor was about 1310 ppm, under a range of limited conditions. The modeling study showed that both the WGS reaction rate and the CO2/H2 selective permeation played an important role on the overall reactor performance.